MANAGEMENT OF ANAPHYLAXIS IN DENTAL OFFICE – AN UPDATE - DR. M.P.SANTHOSH KUMAR, (International Journal of Pharma and Bio Sciences, 2015)
Anaphylaxis is an acute, life threatening systemic reaction, which can be triggered by any commonly used or prescribed agents in dentistry. Dental practitioners must have adequate knowledge about this medical emergency, to diagnose at its earliest onset and provide prompt treatment for the patients. This article reviews about the epidemiology, etiology, pathophysiology, clinical features and differential diagnosis of anaphylaxis. An up-to-date information for assessment and management of anaphylaxis as given by World allergy organization [WAO] guildelines and NICE clinical guideline are summarized.